MCR-1-dependent lipid remodelling compromises the viability of Gram-negative bacteria. Issue 1 (31st December 2022) - Feng, Siyuan; Liang, Wanfei; Li, Jiachen; Chen, Yong; Zhou, Dianrong; Liang, Lujie; Lin, Daixi; Li, Yaxin; Zhao, Hui; Du, Huihui; Dai, Min; Qin, Li-Na; et al.
ABSTRACT: The global dissemination of the mobilized colistin resistance gene, mcr-1, threatens human health. Recent studies by our group and others have shown that the withdrawal of colistin as a feed additive dramatically reduced the prevalence of mcr-1 . Although it is accepted that the rapid reduction in mcr-1 prevalence may have resulted, to some extent, from the toxic effects of MCR-1, the detailed mechanism remains unclear. Here, we found that MCR-1 damaged the outer membrane (OM) permeability in Escherichia coli and Klebsiella pneumonia and that this event was associated with MCR-1-mediated cell shrinkage and death during the stationary phase. Notably, the capacity of MCR-1-expressing cells for recovery from the stationary phase under improved conditions was reduced in a time-dependent manner. We also showed that mutations in the potential lipid-A-binding pocket of MCR-1, but not in the catalytic domain, restored OM permeability and cell viability. During the stationary phase, PbgA, a sensor of periplasmic lipid-A and LpxC production that performed the first step in lipid-A synthesis, was reduced after MCR-1 expression, suggesting that MCR-1 disrupted lipid homeostasis. Consistent with this, the overexpression of LpxC completely reversed the MCR-1-induced OM permeability defect. We propose that MCR-1 causes lipid remodelling that results in an OM permeability defect, thus compromising the viability of Gram-negative bacteria. These findings extended our understanding of the effect of MCR-1 on bacterial physiology and provided a potential strategy for eliminating drug-resistant bacteria.